2016
DOI: 10.4103/0253-7613.186213
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effects of melatonin and caffeic acid phenethyl ester on acute potassium dichromate toxicity and genotoxicity in rats

Abstract: Objective:The aim of this study is to investigate the possible protective effects of melatonin and caffeic acid phenethyl ester (CAPE) on potassium dichromate (K2 Cr2O7)-induced nephrotoxicity and genotoxicity.Methods:A total of 40 Wistar albino rats were divided into five groups: control, K2Cr2O7(K2Cr2O715 mg/kg, one dose, i.p.), K2Cr2O7 + melatonin, K2Cr2O7 + CAPE, and K2Cr2O7 + melatonin + CAPE. Urine and blood samples were collected from rats before scarification. One kidney was collected for histopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“… [ 121 ] GT In vivo study in rats or mice 4–10 mg/kg i.p. Protective effects against genotoxic action of potassium dichromate, cobalt, ethanol, paraquat [ [122] , [123] , [124] , [125] ] GT In vitro study using human lymphocytes 0.2 mM Anti-genotoxic effect on mercuric chloride and gossypol [ 110 , 126 ] CG Transgenic mice at increased risk for prostate adenocarcinoma 10–20 mcg/L in dw 18 weeks Strong prostate cancer inhibitory effect [ 127 ] CG Transgenic mice susceptible for mammary tumours 50–200 mcg/kg per day via gavage 30 weeks Reduced incidence and growth rate of mammary tumours [ 128 , 144 ] CG Rats, mice susceptible for breast cancer 10–20 mcg/L in dw >1 yr No induction of uterine tumours, lower incidence of mammary tumours. [ 129 , 130 ] …”
Section: Safety Of Melatonin Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 121 ] GT In vivo study in rats or mice 4–10 mg/kg i.p. Protective effects against genotoxic action of potassium dichromate, cobalt, ethanol, paraquat [ [122] , [123] , [124] , [125] ] GT In vitro study using human lymphocytes 0.2 mM Anti-genotoxic effect on mercuric chloride and gossypol [ 110 , 126 ] CG Transgenic mice at increased risk for prostate adenocarcinoma 10–20 mcg/L in dw 18 weeks Strong prostate cancer inhibitory effect [ 127 ] CG Transgenic mice susceptible for mammary tumours 50–200 mcg/kg per day via gavage 30 weeks Reduced incidence and growth rate of mammary tumours [ 128 , 144 ] CG Rats, mice susceptible for breast cancer 10–20 mcg/L in dw >1 yr No induction of uterine tumours, lower incidence of mammary tumours. [ 129 , 130 ] …”
Section: Safety Of Melatonin Administrationmentioning
confidence: 99%
“…A full range of genotoxicity tests, including in vitro non-mammalian [ 113 , [116] , [117] , [118] ] and in vitro mammalian cell systems [ 113 , 117 , 119 ], and in vivo mammalian system [ 120 , 121 ] tests consistently found no evidence that melatonin is genotoxic (neither mutagenic or clastogenic). Furthermore, several studies in various in vitro/in vivo systems have reported the anti-genotoxic action of melatonin [ [122] , [123] , [124] , [125] , [126] ], usually ascribed to its antioxidant activity.…”
Section: Safety Of Melatonin Administrationmentioning
confidence: 99%
“…[ 1 ] Cr occurs in several states at oxidation, ranging from +2 to +6. [ 2 ] However, it is unstable except +3 and +6 forms in nature. [ 3 ] Studies have shown that Cr 6+ can affect human health, Cr 3+ is a beneficial micronutrient.…”
Section: Introductionmentioning
confidence: 99%